(untitled) - Richard Wolfson (New York, 1995)
This book is organized into six parts. Part 1 covers the basics of mechanics. Part 2 studies motion in terms of oscillations, waves, and fluids. Part 3 is on thermodynamics. Part 4 deals with electricity and magnetism. Part 5 treats optics. Part 6 briefly introduces modern physics. Each part ends with Cumulative Problems that help students synthesize concepts from several chapters. Part 6 begins with relativity and continues with quantum mechanics and its applications to atoms, molecules, and the solid state; nuclear physics and its applications; and partical physics and cosmology
Keywords: physics